Modeling the Derivatives Market Response under Monetary Policy Regimes: Empirical Evidence from Nigeria (Acta Universitatis Danubius. Œconomica, 2025)
The study examines the response of the derivative market under the monetary policy regimes in Nigeria, Markov-Switching VAR (MS-VAR) approach was employed. The period of investigation spanned 1990q1 to 2023q4. Findings from the study suggest that the internal factors within the financial system have a much greater impact on interest rates than external factors such as inflation, exchange rates or real gross domestic product in the first regime. In the second regime, results suggest that interest rate shocks significantly impact the consumer price index (CPI, or inflation) and the forward exchange rate (FEXR, a proxy for the derivatives market) in the short term, but its effect on RGDP is negligible. This suggests that inflation and forward exchange rates are primarily influenced by changes in monetary policy stance. Suggesting that regulatory agencies minimize their interventions in the market during crises and allow market forces to stabilize fluctuations. This is because such interventions tend to reduce volatility in the short term, without producing lasting effects.